Sex Differences in CMV Replication and HIV Persistence During Suppressive ART. (11th July 2020) - Gianella, Sara; Tran, Sarah McDonald; Morris, Sheldon; Vargas, Millie; Porrachia, Magali; Oliveira, Michelli F; Lada, Steve; Zhao, Mitchell; Ellsworth, Grant B; Mathad, Jyoti S; Wilkin, Timothy
Abstract: Background: The association between subclinical cytomegalovirus (CMV) replication and HIV persistence has not been investigated in cis-gender women with HIV. Methods: Fifty virologically suppressed female participants with HIV were prospectively enrolled and provided oral, vaginal, and urine samples and peripheral blood mononuclear cells at 1 cross-sectional time point. CMV DNA was quantified in each specimen by real-time polymerase chain reaction (PCR). Cellular HIV DNA and HIV RNA transcripts (unspliced and multiply spliced [ms] encoding tat-rev) were quantified by droplet digital (dd) PCR in peripheral blood cells. Forty-nine male individuals with HIV and CMV (historical data) were used as controls. Results: Levels of cellular HIV DNA and unspliced HIV RNA were not different between sexes, but female participants had less detectable msHIV RNA and CMV DNA compared with males (both P < .01). Unlike previously described for males, the presence of CMV DNA was not associated with increased HIV DNA in females. Among female participants, premenopausal status was independently associated with lower HIV DNA compared with postmenopause, after adjusting for nadir CD4 count ( P < .01). Conclusions: Female participants with HIV had reduced cellular HIV RNA and less subclinical CMV DNA compared with males but overall similar HIV DNA levels in our study. Postmenopausal status was independently associated with higher HIV DNA levels among female participants.